TP8.2.21 Two Teams, One Patient: Identifying Barriers to Patients' Flow from Emergency Departments to Surgical Wards. (28th October 2021) - Morris, Lucy; Tarazi, Munir; Waugh, Christopher; Foster, Karl; Shah, Jigar; Mansour, Moustafa
Abstract: Aims: The transfer of responsibility for patient care across the Emergency Department (ED)/ inpatient interface has always been recognised as a challenging process. Current research focuses on qualitative data and is based occasionally on anecdotal information. The aim of this study was to identify barriers to efficient patient flow with a specific focus on type and quality of referrals and logistics involved. Methods: Quantitative retrospective data was collected on referrals received by the surgical team from ED (n = 83). The outcome of the referral was recorded. Quality of referrals was assessed on clinical information, examination and investigations performed as well as working diagnoses. Further data was collected on location and time to review referred patients. Results: Outcome of referral: 14.5% were discharged directly from ED, 16.9% were admitted for <24 hours, 4.8% were referred to another speciality within 24 hours and 63.9% were admitted for > 24 hours. Quality of referral: 18.1% patients were referred without working diagnosis. 31% of patients presenting with upper abdominal pain did not have amylase checked prior to referral and 20% of patients with suspected PR bleeding lacked a PR examination. Logistics: 57% of patients were seen in ED. 15.7% were reviewed within 1 hour (median: 133mins). Conclusions: Referrals often failed to meet the needs/criteria of the speciality team. Combining the above with high volume of referrals and logistical challenges of working across multiple areas leads to potential delays in timely patients' review. Intense workloads create stressful environments which eventually breed interpersonal discord.